Co-immunization with recombinant S5196–272 and S6200–317 proteins for enhanced protective antibody response against Tilapia lake virus in Nile tilapia, Oreochromis niloticus (Linnaeus, 1758) - Plysup, Benjamaporn; Lueangyangyuen, Apisit; Khrisanapant, Prit; Senapin, Saengchan; Rattanarojpong, Triwit; Somsoros, Wasusit; Khunrae, Pongsak; Sangsuriya, Pakkakul (Agriculture and Natural Resources, 2026)
Importance of the work: Co-immunization with recombinant S5196–272 and S6200–317 proteins enhances protective immunity and provides insights for future TiLV vaccine development. Objectives: To evaluate the vaccine potential of combined S5196–272 and S6200–317 compared to individual immunization. Materials and Methods: A sample of Nile tilapia was divided into three main groups: immunized with S5196–272 and S6200–317 individually, or co-immunized. Antibody responses were measured weekly using enzyme-linked immunosorbent assay, with virus neutralization being assessed using a methylthiazolyldiphenyl-tetrazolium bromide (MTT) cell viability assay. A viral challenge test was conducted to determine the relative percentage of survival (RPS). Results: Co-immunization of the fish with S5196–272 and S6200–317 resulted in a synergistic effect, leading to the higher production of S6200–317-specific antibodies than for immunization with S6200–317 alone. A significant increase in serum antibody levels was observed from 7 d, 21 d, 28 d and 35 d post-co-immunization. In contrast, S5196–272-specific antibodies were generated at consistently high levels following both individual and co-immunization. The MTT cell viability assay findings demonstrated that antibodies from the co-immunization group had the highest virus-neutralizing effect (87.22% viability). Furthermore, the viral challenge assay revealed that the co-immunization group had the highest RPS (57.14%), whereas individual immunization provided no protection effect against TiLV infection. Main finding: Co-immunization with S5196–272 and S6200–317 induced a synergistic antibody response and provided effective protection against TiLV in Nile tilapia.